2023
DOI: 10.62222/xqko8567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of demographic characteristics of enterprises on the implementation of corporate social responsibility in SMEs context

Janka Betakova,
Michal Bernard Pietrzak,
Bartłomiej Igliński

Abstract: Research background: Corporate social responsibility (CSR) is a rapidly developing field within business management, the effects of which manifest themselves in the practical management of organisations. At present, research within academia is focusing on the analysis and evaluation of the demographic characteristics of enterprises on entrepreneurs’ attitudes towards the implementation of socially responsible business management practices. Purpose of the article: The purpose of the article is to quantify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…This research has confirmed the importance of CSR implementation for the sustainability of SMEs, which is in line with the conclusions of Graafland and Noorderhaven (2020), Grimstad et al (2020), andBelas et al (2022). It is widely accepted that CSR enhances the performance of SMEs by increasing competitiveness (Apospori, 2018) because of the moderating role of diverse CSR factors, such as regional aspects (Rashiti & Skenderi, 2023), engaged and loyal employees (Castro-González et al, 2021), and improved firm image and reputation (Feng et al, 2022;Kim et al, 2022;Qing & Jin, 2022;Betakova et al, 2023).…”
Section: Discussionsupporting
confidence: 86%
“…This research has confirmed the importance of CSR implementation for the sustainability of SMEs, which is in line with the conclusions of Graafland and Noorderhaven (2020), Grimstad et al (2020), andBelas et al (2022). It is widely accepted that CSR enhances the performance of SMEs by increasing competitiveness (Apospori, 2018) because of the moderating role of diverse CSR factors, such as regional aspects (Rashiti & Skenderi, 2023), engaged and loyal employees (Castro-González et al, 2021), and improved firm image and reputation (Feng et al, 2022;Kim et al, 2022;Qing & Jin, 2022;Betakova et al, 2023).…”
Section: Discussionsupporting
confidence: 86%
“…According to Ortiz-Martinez et al (2023), we might define CSR as the microeconomic part of the larger macroeconomic idea of sustainability, so CSR is perceived as a tool of sustainability. Betakova et al (2023) found that demographics characteristics as ia age, level of education or business sectors play kay role in CSR implementation. Skypalova et al (2023) realised empirical research on the 360 Slovak and Czech enterprises.…”
Section: H4: Applying Ethics In Business Has a Positive Effect On The...mentioning
confidence: 99%
“…Cultural and social contexts significantly influence the effectiveness of environmental initiatives in the public sector, with non-Western contexts showing varied levels of formalism in policy implementation [2]. Corporate social responsibility (CSR), present also in small and medium-sized enterprises (SMEs), shows that demographic characteristics such as company size and the educational level of entrepreneurs significantly influence CSR perceptions and practices, and these are crucial for the long-term sustainability of businesses, especially in the current context [3].…”
Section: Introductionmentioning
confidence: 99%